2005
DOI: 10.1038/sj.bjp.0706341
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the biological activities of anagrelide and its major metabolites in haematopoietic cell cultures

Abstract: 1 The platelet-lowering drug anagrelide inhibits bone marrow megakaryocytopoiesis by an unknown mechanism. Recently, it was found that anagrelide is bio-transformed in humans into two major metabolites (6,7-dichloro-3-hydroxy-1,5 dihydro-imidazo[2,1-b]quinazolin-2-one (BCH24426) and 2-amino-5,6-dichloro-3,4,-dihydroquinazoline (RL603). Whether these metabolites have biological activities that may underlie the mode of action of the parent drug is presently unclear. To clarify this question here we have compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 23 publications
3
32
0
1
Order By: Relevance
“…Also tested in PDE4D (390 nM) . Anagrelide (13); zardaverine (14); CDP 840 (15); trequinsin (16); piclamilast (17); YM 976 (18); cilostamide (19, 20); milrinone (21); (R)-(−)-rolipram (22); Ro 20-1724 (23); cilostazol (24); siguazodan (21); RS 25344 (25); ICI 63197 (26) .…”
Section: Resultsunclassified
“…Also tested in PDE4D (390 nM) . Anagrelide (13); zardaverine (14); CDP 840 (15); trequinsin (16); piclamilast (17); YM 976 (18); cilostamide (19, 20); milrinone (21); (R)-(−)-rolipram (22); Ro 20-1724 (23); cilostazol (24); siguazodan (21); RS 25344 (25); ICI 63197 (26) .…”
Section: Resultsunclassified
“…This activity led to the registration of anagrelide as an agent for lowering platelet count in patients with myeloproliferative disorders. The mechanism of this activity has not been characterized as yet but appears to act at the megakaryocyte level -inhibiting platelet production [106].…”
Section: Clinical History Of Pde3 Inhibitorsmentioning
confidence: 99%
“…In vitro studies have shown that anagrelide is metabolized by cytochrome P450 (CYP) 1A2 and produces the active metabolite 6,7-dichloro-3-hydroxy-1,5-dihydro-imidazol[2,1-b] quinazolin-2-one (3-hydroxyanagrelide) [4, 5]. Caffeine is a known substrate of CYP1A2 [6] and the possible effects of the constituents of a normal high-fat breakfast with coffee on the rate and extent of absorption of anagrelide, as well as the rate and extent of formation of the active metabolite, was considered worthy of investigation.…”
Section: Introductionmentioning
confidence: 99%